2022
DOI: 10.3390/educsci13010036
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Implementation of an Innovative Course on the Creation of Cultural Landscape Images: A Case Study of Dalin Township in Taiwan

Abstract: Innovative design-based education is a student-centered approach that aims to nurture students’ proactivity, creativity, and interdisciplinary integrated skills. The curriculum planning of a course in this study incorporated design-based learning with the 4D design process. Three units were planned: field exploration and concept development, 3D wearable creations, and cultural landscape shaping. Each unit was co-taught by an interdisciplinary teacher. By means of teamwork, the students explored agricultural sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The research findings indicate that design practices rooted in the biomimicry approach yield positive outcomes across various aspects of student development. According to Hu (2023), these practices enhance students' communication abilities, foster collaborative interactions with peers, bolster domain-specific cognitive skills, shape a positive perception of technology's value, boost self-confidence, and elevate motivation and attentiveness levels. Furthermore, biomimetic projects serve as potent vehicles for knowledge and skill acquisition while instilling a mindset of sustainability and cyclical thinking (Gardner, 2012).…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The research findings indicate that design practices rooted in the biomimicry approach yield positive outcomes across various aspects of student development. According to Hu (2023), these practices enhance students' communication abilities, foster collaborative interactions with peers, bolster domain-specific cognitive skills, shape a positive perception of technology's value, boost self-confidence, and elevate motivation and attentiveness levels. Furthermore, biomimetic projects serve as potent vehicles for knowledge and skill acquisition while instilling a mindset of sustainability and cyclical thinking (Gardner, 2012).…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
“…The effect of the biomimetic approach on the learner's affective characteristics and social skills: Although biomimicry studies are not directly aimed at developing affective characteristics, it has been established that learning motivation, leadership, collaborative work, environmentally friendly behaviours, as well as cognitive processes, contribute positively to students' affective characteristics and social skills. Research findings indicate that design practices based on the biomimicry approach positively improve students' communication, cooperation with peers, cognitive field skills and value perceptions towards technology (Hu, 2023). For example, in the study conducted by Yıldız (2023), when students' awareness of the biomimicry approach was established, it was observed that students' awareness of their environment and examples from nature increased and they began to give more examples, particularly of living behaviours.…”
Section: Figure 4 Distribution Of Subdomains Associated With Learning...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, a case study of an innovative course that aims to promote the creation of cultural landscape images in Dalin Township, Taiwan, was presented [9]. The course combined both theoretical and practical components, using diverse teaching methods to engage students and promote their participation.…”
Section: Contribution 6: the Design And Implementation Of An Innovati...mentioning
confidence: 99%